A Fluid-Solid-Magnetic Coupling Algorithm of Internal Crack Growth in the Weld of Oil and Gas Pipelines. (3rd October 2018) - Cui, Wei; Song, Rixuan; Xia, Fafeng; Zhang, Qiang; Wang, Peter
Abstract : In order to characterize the dynamic process of the crack growth in the weld of oil and gas pipelines, a mathematical model of fluid-solid-magnetic multifield coupling was constructed in this paper. Based on this model, the bidirectional fluid-solid coupling and unidirectional magnetic structure coupling caused by the weld deformation were achieved by dynamic application of the fluid permeation pressure, calculating the internal crack growth in the pipe weld, reconstructing the computational grid near the internal crack, and discussing the characteristics of the magnetic leakage field in the process of the internal crack growth in pipe weld. Thus, a fluid-solid-magnetic coupling algorithm for the internal crack growth in pipe welds considering fluid permeation pressure is established. According to the characteristics of the internal crack opening distance, internal crack growth length, crack tip energy release rate, peak values of magnetic induction intensity level, and vertical component, the process of the internal crack growth is measured. The results show that the fluid osmotic pressure accelerates the process of the internal crack growth and this algorithm can solve the problem of the characterization and evaluation of crack growth in pipe welds under fluid-solid-magnetic coupling action.